Evaluation of hand skin radiation doses from accidental 131I and 18F radiopharmaceutical contamination during nuclear medicine procedures - Akbar Abbasi; Vali Bashiry; Fatemeh Mirekhtiary; Serap Maden; Ahmed H Ali (Radiation Protection Dosimetry, 2026)
Abstract Iodine-131 (131I) and fluorine-18 (18F) are widely used radionuclides in nuclear medicine; however, accidental localized contamination of the hands may occur during radiopharmaceutical preparation, dispensing, administration, or contaminated-material handling. This study presents a scenario-based computational assessment of hand skin dose from 131I and 18F contamination using the SkinDose module of VARSKIN/V+. Skin equivalent dose coefficients were calculated as a function of exposure time and normalized per unit spilled activity as mSv/MBq. For 18F, the cumulative dose increased rapidly during the first few hours and approached a plateau due to its short physical half-life. For 131I, dose accumulation continued over the evaluated period because of its longer physical half-life. The results provide practical reference dose coefficients for radiation-protection assessment of localized hand contamination, while emphasizing that they should be interpreted within the limits of the defined scenarios and realistic contamination-management conditions.